Mindfulness is associated with the weight status, severity of disease, and severity of extra-intestinal symptoms among individuals with irritable bowel syndrome - Aghamohammadi, Vahideh; Rezakhani Moghadam, Hamed; Najafi, Esmail; Nasiri, Khadijeh; Hamidi, Hanane; Hajizadeh, Mohaddese; Zamani, Parastou; Lotfi Yaghin, Neda; Bazyar, Hadi; Najafipour, Farzad (Frontiers in Psychology, 2025)
ObjectivesConsidering the high prevalence of irritable bowel syndrome (IBS), high medical costs, and the lack of complete treatment, paying attention to the psychological processes of these patients can lead to providing cognitive solutions to eliminate or reduce pain, and improve its consequences and psychological effects. Accordingly, the current study aims to evaluate the relationship between mindfulness and quality of life, IBS symptom severity, severity of extra-intestinal symptoms, and obesity among a cross-sectional sample of patients with IBS.MethodIn this analytical cross-sectional study, 110 adults with IBS were confirmed according to Rome IV criteria by a physician. They were selected using cluster sampling. Various questionnaires and tools, including sociodemographic, physical activity, 24-item Five Facet Mindfulness Questionnaire Short Form (FFMQ–24), IBS-Quality of Life Instrument (IBS-QOL), IBS Symptom Severity Scale (IBS-SSS), and IBS Extra-intestinal Symptom Severity Scale (IBS-EISSS) were applied. SPSS software version 23 (IBM SPSS Statistics, Armonk, USA) was used for data analysis.ResultsInverse significant association was observed between the mindfulness score and BMI, Global IBS-SSS score, and Global IBS-EISSS score (p < 0.05). Moreover, the mindfulness score was inversely associated with weight in adjusted models (model 2: B = −0.16, p = 0.02; model 3: B = −0.21, p = 0.002). Mindfulness was associated with fewer odds of being overweight and obese in patients with IBS (OR = 0.93, CI: 0.87–0.98).ConclusionMindfulness had a significant relationship with obesity, the IBS symptom severity, as well as severity of extra-intestinal symptoms among those who suffer from IBS.